1991
DOI: 10.4315/0362-028x-54.7.549
|View full text |Cite
|
Sign up to set email alerts
|

An Update Survey of Bulk Tank Milk Quality in Vermont

Abstract: Quality of Vermont bulk tank milk was first surveyed in 1985 as part of a statewide milk quality enhancement program. In a second survey conducted in 1990, bulk tank milk from 1,971 farms was sampled and tested for standard plate count, bacterial type and species distribution, and somatic cell count. Test results from 1,203 duplicate bulk tank milk samples were compared between five Vermont milk processors and the University of Vermont Quality Milk Research Laboratory. Arithmetic mean standard plate count cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…We observed a positive association between SCC and CC, which has been consistently reported in previous studies (Goldberg et al, 1991;Jayarao et al, 2004;Rysanek and Babak, 2005;Pantoja et al, 2009) and suggests that milking of mastitic cows can increase CC. During the course of this study, farmers frequently asked whether milking of mastitic cows could cause sudden increases ("spikes") in CC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed a positive association between SCC and CC, which has been consistently reported in previous studies (Goldberg et al, 1991;Jayarao et al, 2004;Rysanek and Babak, 2005;Pantoja et al, 2009) and suggests that milking of mastitic cows can increase CC. During the course of this study, farmers frequently asked whether milking of mastitic cows could cause sudden increases ("spikes") in CC.…”
Section: Discussionsupporting
confidence: 90%
“…The mean CC of BTM has been reported to be 31 (n = 855 milk samples; Boor et al, 1998), 37 (n = 33,020 milk samples; Rysanek and Babak, 2005), and 70 cfu/mL (n = 504 milk samples; Jayarao et al, 2004). Goldberg et al (1991) reported that about 50% of the 1,203 BTM samples collected from Vermont herds had CC >500 cfu/mL, whereas Jayarao et al (2004) reported that 50% of 504 BTM samples collected from herds in Pennsylvania had CC ≥60 cfu/mL. Most CC reported in recent studies would not meet the regulatory limit of 10 cfu/mL used in some US states that allow sale of unpasteurized milk.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were seen in a study conducted by Goldberg et al (1991) in a herd with SCC average of 918,000 cells/ml before blitz therapy; it was reduced to 439,000 cells/ml 30 days after treatment. Before treatment, 40 animals positive for S. agalactiae were responsible for 47.04% of SCC in bulk tank milk; this value was reduced to 18.48% after removing S. agalactiae, proving the role of this agent in the high incidence of SCC in the herd.…”
Section: Discussionsupporting
confidence: 86%
“…Increased numbers of environmental organisms and Staphylococcus spp. on BTM suggest that equipment sanitation and/or udder preparation procedures are insufficient (Goldberg et al 1991). After it leaves the udder, milk may become contaminated with microorganisms from the surfaces of the cow, from the environment and from unclean milking systems (Hayes, 1995; Richter & Vedamuthu, 2001).…”
Section: Discussionmentioning
confidence: 99%